Comparison of Offender and Non-offender Young Men to Setting Goals for Life and Attributing Meaning to Life - Eryilmaz, Ali (SPRINGER, 2018)
The main goal of the present study is to compare male offenders and non-offenders in terms of how they attribute meaning to life and set life goals. The samples were chosen from among offenders (n = 50) and non-offenders (n = 50) who were between ages 19-26. Mixed method was used in this study. The scale of setting life goals and interview form were used to collect data. To analysis of the data, the content analysis technique and t test and were used. Findings of the present study show that offenders tend to have troubles setting life goals when compared to non-offenders. Furthermore, the results of this study could be used in rehabilitating offenders and preventing those at risk of committing criminal acts from doing so.
Keywords: Meaning of life; Life goals; Offenders; Young men; NEED-SATISFACTION; DELINQUENCY; DESISTANCE; CHAPLAINCY; ADULTHOOD; HAPPINESS; BEHAVIOR; HEALTH; MATTER; MODEL; Public, Environmental & Occupational Health; Religion